Intelligent and Autonomous: Transforming Values in the Face of Technology - Kalpokas, Ignas; Kalpokienė, Julija (Value Inquiry Book Series, 2023)
This book uses case analyses and industry insights and blends them with forays into philosophy and ethics to conceptualise the mismatch between human values and the values inherent in an increasingly technologized world. Bringing together contributors from the disciplines of law, politics, philosophy, and communication studies, this volume develops an interdisciplinary vocabulary for thinking about the questions and antinomies of human-technology interaction while also resisting any deceptively straightforward synthesis. The topics discussed include the competition over and regulation of technology, the harm induced by autonomous technologies, and the place and role of humans in a world that is undergoing rapid and radical change.